Perlindungan HAM Korban Pelecehan Seksual Pada Wilayah Hukum Kepolisian Resor Kendal - Septiawan, Ilham (Jurnal Kewarganegaraan, 2024)
AbstractHuman Rights (HAM) are the nature of every human being and must continue to be upheld. Protection and enforcement of human rights are also proof of justice, including for victims of sexual harassment. Criminal acts of sexual harassment have also occurred in the jurisdiction of the Kendal Police, where, in recent years, there have always been cases of sexual harassment. This research aims to provide an overview of the efforts made by the Kendal Police to provide human rights protection to victims of sexual harassment in the Kendal area. The results of this research conclude that the protection and enforcement of human rights for victims of sexual harassment in the jurisdiction of the Kendal Police is, of course, appropriate by imposing penalties on perpetrators of sexual harassment as stated in Articles 414 to Article 422 of Law Number 1 of 2023. However, apart from that, the Government is also responsible for providing protection and upholding human rights for women who are victims of sexual harassment. The Kendal government assists in medical services, legal assistance, and recovery efforts carried out by various parties.-------------------AbstrakHak Asasi Manusia (HAM) menjadi fitrah setiap manusia yang harus terus dipegang dan ditegakkan. Perlindungan dan penegakan HAM juga menjadi sebuah bukti keadilan termasuk di dalamnya bagi korban pelecehan seksual. Tindak kriminal pelecehan seksual turut terjadi di wilayah hukum Polres Kendal yang pada beberapa tahun terakhir selalu terjadi kasus pelecehan seksual. Penelitian ini bertujuan untuk memberikan gambaran mengenai apa saja upaya yang dilakukan oleh Polres Kendal untuk memberikan perlindungan HAM pada korban pelecehan seksual di wilayah Kendal. Hasil dari penelitian ini menyimpulkan bahwa perlindungan dan penegakan HAM bagi korban pelecehan seksual di wilayah hukum Polres Kendal tentu saja sudah tepat. Dengan adanya pemberlakuan hukuman kepada pelaku pelecehan seksual seperti telah tercantum dalam Pasal 414 sampai pasal 422 Undang-Undang Nomor 1 Tahun 2023. Namun selain itu, Pemerintah juga bertanggung jawab memberikan perlindungan dan penegakan HAM terhadap Perempuan korban pelecehan seksual. Pemerintah Kendal memberikan pemberian bantuan seperti layanan medis, bantuan hukum, dan upaya pemulihan yang dilakukan oleh berbagai pihak.